Endoscopic Esophageal Submucosal Tunnel Dissection for Cystic Lesions Originating from the Muscularis Propria of the Gastric Cardia. (20th August 2020) - Liu, Lu; Guo, Hai-Mei; Miao, Feng; Li, Nuo; Jiao, Shu-Hua; Cai, Shuang; Liu, Peng-Liang; Zhang, Shan-Shan; Ma, Jia; Weng, Yang; Sun, Ying; Tang, Yin-Si; et al.
Abstract : Objective . To analyze the types and properties of cystic lesions originating from the muscularis propria of the gastric cardia (CLMPGC), explore the growth pattern and anatomical characteristics, and evaluate the safety, feasibility, and clinical efficacy of endoscopic esophageal submucosal tunnel dissection (ESTD). Methods . From September 2013 to July 2018, we treated 6 patients with CLMPGC whom we had diagnosed using endoscopy, endoscopic ultrasound (EUS), and Computed Tomography (CT) before the operations. ESTD was the best option for treatment for all these patients. Postoperative observation and follow-ups were performed, and the operational, clinical data, and treatment results are analyzed. Results . The mean age of the patients was 50.67 ± 11.59 years (male : female = 1 : 1). The only clinical manifestations the patients exhibited were upper abdominal discomfort. The diameter of the masses was 2.05 ± 0.73 (1.1–3.0) cm. The duration of the ESTD operation was 93.5 (82–256) mins, and the length of hospital stay was 7.50 ± 1.38 days. Postoperative pathology showed 4 cases of an epithelioid cyst, and 2 cases of mucocele with xanthogranuloma. There were no complications, such as hemorrhage, pneumothorax, and pleural effusion during and after the operation. No recurrence during the follow-ups was observed. Conclusion . The CLMPGC were mainly mucocele and epidermoid cyst, in an expansive growth pattern, and these lesions had no distinct borders with the muscularis propria. The muscularis propria formed a complete wall of the lesion. There was no direct blood supply to the lesions from big blood vessels. Endoscopic esophageal submucosal tunnel dissection was a safe, feasible, and effective treatment for CLMPGC.